2015
DOI: 10.1177/0146167215615335
|View full text |Cite
|
Sign up to set email alerts
|

Approach–Avoidance Training Effects Are Moderated by Awareness of Stimulus–Action Contingencies

Abstract: Prior research suggests that repeatedly approaching or avoiding a stimulus changes the liking of that stimulus. In two experiments, we investigated the relationship between, on one hand, effects of approach-avoidance (AA) training on implicit and explicit evaluations of novel faces and, on the other hand, contingency awareness as indexed by participants' memory for the relation between stimulus and action. We observed stronger effects for faces that were classified as contingency aware and found no evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 56 publications
7
42
1
Order By: Relevance
“…Note, however, that this explanation does not fit well with the observation that most of the participants were surprised by hearing the study aim. Fourth, previous research provided support for the moderating effects of contingency awareness on implicit and explicit stimulus evaluations [ 27 , 48 ]. In future research, it would therefore be interesting to evaluate whether contingency awareness moderates the effects of gamified approach-avoidance training and verbal suggestions on food-related outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…Note, however, that this explanation does not fit well with the observation that most of the participants were surprised by hearing the study aim. Fourth, previous research provided support for the moderating effects of contingency awareness on implicit and explicit stimulus evaluations [ 27 , 48 ]. In future research, it would therefore be interesting to evaluate whether contingency awareness moderates the effects of gamified approach-avoidance training and verbal suggestions on food-related outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…The contribution of the present project is twofold. First, we show that, in addition to other forms of evaluative learning such as mere exposure (34), Pavlovian learning (35), approachavoidance training (36), and verbal instructions (12), implicit evaluations of stimuli, similar to their explicit counterparts, are amenable to updating as a result of reinforcement learning, i.e., experience with the positive and negative outcomes of actions involving those stimuli. Second, we demonstrate a commonality and a difference in the computations underpinning the updating of explicit vs. implicit evaluations via reinforcement learning: just like explicit evaluations, implicit evaluations were found to be responsive to model-free processes at baseline and following initial model-free learning with different reinforcement contingencies.…”
Section: Discussionmentioning
confidence: 96%
“…First, a large body of research has provided evidence that value representations in humans, as revealed by explicit measures of self-report, can be updated on the basis of the rewards received as a result of interacting with a given stimulus (29)(30)(31)(32)(33). However, despite a similarly large body of research investigating the effects of mere exposure (34), Pavlovian learning (35), approach-avoidance training (36), and verbal instructions (12) on implicit evaluations, to our knowledge, the effects of reinforcement learning, i.e., rewarding or punishing participants for taking actions involving motivationally relevant stimuli, on implicit evaluations has never been investigated. As such, the first goal of the present project is to establish whether implicit evaluations of novel stimuli can be effectively shifted via this form of learning.…”
Section: The Present Projectmentioning
confidence: 99%
“…Because the current research investigates motor actions as an antecedent (rather than a consequence) of evaluation, research using arm flexion/extension as manipulation of affective and motivational states (i.e., action-to-affect) is more directly relevant. The published action-to-affect research largely supports the hypothesis that arm flexion induces approach motivation and that arm extension induces avoidance motivation (Cacioppo et al, 1993;Centerbar & Clore, 2006;Friedman & Förster, 2008;Slepian et al, 2012;Van Dessel et al, 2016; for an exception, see Rotteveel et al, 2015).…”
Section: Approach-and Avoidance-related Motor Actionsmentioning
confidence: 81%